The Use of Traditional Games to Implement Character Education Policy in Kindergarten - Hendrowibowo, Lorensius; Haryono, Haryono; Raharjo, Tri Joko; Rusdarti, Rusdarti (The Journal of Educational Development, 2018)
The background of this research is an emerging problem in the field of education in Indonesia. One of the problems is the occurrence of moral irregularities among students which results in the moral decline of the nation. At the level of early childhood education, character education is a way that can be implemented to overcome these problems. One way is to implement various traditional games. This study aims to explain the implementation of character education based on traditional games, the process of internalizing character values based on traditional games, and the possibility of applying traditional games as a character education model. This is a qualitative research conducted in three Kindergartens IN Gunung Kidul, Yogyakarta; each with a background of Islam, State and Christianity. The primary data of this study were sourced from the results of interviews with informants. The secondary data were in the form of policies, values, school views, and parents functioning further to strengthen the data and as a means of character education configuration based on traditional games in the context of micro systems. The data were analyzed through several stages, namely (1) display of observation and interview results; (2) sorting out observations and interviews; (3) discovery of contrasting or negative elements. The results of this study show that (1) The implementation of character education based on traditional games in the three kindergartens is different from one another; (2) character values are internalized through several traditional games, namely gobag sodor, cublak-cublak suweng, dakon, jamuran, and engklek or sundamanda; (3) Character education based on workable traditional games becomes a character education model in kindergarten.